Estimating Global Poverty in Stata : The PovcalNet Command - Castaneda Aguilar, R. Andres; Lakner, Christoph; Prydz, Espen B.; Soler Lopez, Jorge; Wu, Ruoxuan; Zhao, Qinghua (World Bank, Washington, DC, 2019)
This note describes how poverty measures reported by the World Bank can be replicated using the Stata command povcalnet. Users can estimate poverty at any poverty line for the world, regions or sets of countries, by directly querying the World Bank's database of household surveys. The command also retrieves inequality statistics provided by the database.